2019
DOI: 10.31227/osf.io/t6gfs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lampiran Data

Abstract: This study describes the information system and transparency of a free school program that uses a qualitative approach with a case study method. The techniques and procedures for data collection include interviews and direct observation. The validity of the data is done through credibility, flexibility, dependability, and commitment. Data analysis consists of testing, categorizing, tabulating, or combining based on the focus of the research. Based on data analysis, the school information system is free in MUBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…By performing female circumcision, her vital organs are mortgaged by her parents to fulfil the sexual needs of the child's partner in the future. 16 In Indonesia, women still face cultural violence produced by conservative religious ideology. The Directorate of Indigenous Communities of the Directorate General of Culture of the Ministry of Education and Culture (Kemdikbud) found that the people of West Nusa Tenggara (NTB) believed uncircumcised women would find it difficult to get a mate and no one would want to marry them.…”
Section: The History and Culture Of Female Circumcisionmentioning
confidence: 99%
“…By performing female circumcision, her vital organs are mortgaged by her parents to fulfil the sexual needs of the child's partner in the future. 16 In Indonesia, women still face cultural violence produced by conservative religious ideology. The Directorate of Indigenous Communities of the Directorate General of Culture of the Ministry of Education and Culture (Kemdikbud) found that the people of West Nusa Tenggara (NTB) believed uncircumcised women would find it difficult to get a mate and no one would want to marry them.…”
Section: The History and Culture Of Female Circumcisionmentioning
confidence: 99%
“…Pasien dengan risiko tinggi untuk terjadinya depresi respirasi seperti pada orang-orang yang dengan morbid obese dengan sleep apnea dan apabila mereka memiliki dampak respiratorik yang buruk di asosiasikan dengan opioid. 21…”
Section: Nyeri Pasca Operasi Pada Erasunclassified